2020
DOI: 10.1002/celc.202000238
|View full text |Cite
|
Sign up to set email alerts
|

Alkali Metal Cation Incorporation in Conductive TiO2 Nanoflakes with Improved Photoelectrochemical H2 Generation

Abstract: In this research, we investigate the effect of alkali metal cations including Li, Na and Cs in hydrothermal solution on the morphology, stability, and photoactivity of nanostructured TiO 2 nanoflakes as a photoanode. The TiO 2 nanoflakes are formed through hydrothermal treatment of Ti foil in 1.0 M LiOH, NaOH or CsOH at 100°C for 3 h. By subsequent thermal reduction of the structure in an optimized Ar/H 2 environment, conductive TiO 2 nanoflakes were formed. The reduction treatment remarkably improves the phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Low‐bandgap ceramic oxides such as TiO 2 , BiVO 4 , WO 3 , SnO 2 , Fe 2 O 3 , Cu 2 O, and CuO are considered among promising electrode materials for conducting half water‐splitting. [ 141,150–155 ] Figure illustrates the band edge position and the bandgap of some promising metal oxides that have attracted great attention during the past decade. These materials have specific conduction band (CB) and valence band (VB) edge potentials with different positions compared to water oxidation–reduction half potentials.…”
Section: Overview Of Using Metal‐oxide‐based Electrodes In Pec Water Splittingmentioning
confidence: 99%
“…Low‐bandgap ceramic oxides such as TiO 2 , BiVO 4 , WO 3 , SnO 2 , Fe 2 O 3 , Cu 2 O, and CuO are considered among promising electrode materials for conducting half water‐splitting. [ 141,150–155 ] Figure illustrates the band edge position and the bandgap of some promising metal oxides that have attracted great attention during the past decade. These materials have specific conduction band (CB) and valence band (VB) edge potentials with different positions compared to water oxidation–reduction half potentials.…”
Section: Overview Of Using Metal‐oxide‐based Electrodes In Pec Water Splittingmentioning
confidence: 99%
“…From the samples’ CV curves in dark conditions, it is apparent that the area under the curve is dramatically increased for Ru-doped TNTs after Ar/H 2 treatment at 550 °C. This is due to nonfaradic processes that occurred at the surface of the electrode, increasing the active surface area and the number of active sites for the electrocatalytic process and improving the conductivity. ,, …”
Section: Resultsmentioning
confidence: 99%
“…This is due to nonfaradic processes that occurred at the surface of the electrode, increasing the active surface area and the number of active sites for the electrocatalytic process and improving the conductivity. 20,40,41 Figure 4f illustrates the impedance modulus of the pristine and Ru-doped TiO 2 nanotubes before and after hydrogenation treatment. The Bode diagram results indicate that both To further gain insight into the interplay between the photoactivity and the light absorption of Ru-doped TiO 2 under Ar/H 2 reduction, we prepared photoanodes at different reduction temperatures (500, 550, 600, and 650 °C).…”
Section: Resultsmentioning
confidence: 99%
“…For TiO 2 nanotubes, for example, vast studies have been investigated to grow nanotubes with controlled length and thickness by changing the chemical composition of the electrochemical bath [25,26]. Recently, we have reported the growth of TiO 2 nano akes on Ti substrate in alkaline media including LiOH, NaOH and CsOH and investigated the PEC hydrogen generation of the resulted photoanodes [11]. Results showed that the nano akes produced in NaOH alkali solution shows the most stable morphology after thermal treatment and higher photoelectrochemical performance, compared to nano akes formed in other alkali solutions.…”
Section: Introductionmentioning
confidence: 99%